The Effect of Work Motivation and Reward System on Employee Performance at Travel Agent: Case Study Travelinn - Nugraha, Rizki Nurul; Sarinah, Lisa (West Science Social and Humanities Studies, 2024)
This study discusses the effect of work motivation and the Reward system on employee performance at a travel agent in the Menteng area. The research method used is quantitative. This study uses primary data using a questionnaire which is then distributed to respondents, namely 10 employees who are at Travelinn. Data collection is also by direct observation. Descriptive statistics are used to provide an overview of data from work motivation variables, reward systems and employee performance, as well as the distribution of items from each variable. The inferential analysis used in this study is multiple linear regression involving the t test and F test. The results showed that work motivation has a positive and significant effect on employee performance and the Reward system also has a positive and significant effect on employee performance. It is recommended to travel agent management to focus on work motivation factors and reward systems that can improve employee performance. This research also confirms the importance of paying attention to motivational and reward factors in achieving organizational goals in the travel industry.